Study on characteristic of fluid soil in the chamber of EPB shield - Atsushi KAGAWA; Yoshihide SUWA (Nihon Kikai Gakkai ronbunshu, 2021)
The visualization system has been developed to control the fluidity of the excavated soil in the chamber of the EPB shield in real time during the shield advance. For further improvement of the visualization system, agitation tests of the fluid sand mixing with CMC aqueous solution as a thickening material or rheological form to enhance fluidity have been carried out to clarify its flow property. It was confirmed by the tests that the agitating flapper torque of the fluid sand decreased with the increase of the number of flapper rotations. It is assumed that above-mentioned phenomenon was caused by the friction in-between the sand particles. Therefore, the fluidity property of the fluid sand is not exactly same as the general viscous fluid materials. It is, however, useful to evaluate this phenomenon in a numerical formula using the power-law model for the flow property in which shear stress decreases with the increase of the shearing deformation rate, and to apply the formula to numerical analysis, if the analysis is able to simulates the fluid sand behavior with high accuracy. As a result of the agitating tests, the formulas based on power-law model applied negative value to the power index was proposed to evaluate the flow property of the fluid sand.